2017
DOI: 10.14260/jemds/2017/527
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Difference Between Smoker and Non- Smoker Chronic Obstructive Pulmonary Disease

Abstract: BACKGROUNDSmoking is one of the major risk factor associated with COPD. Other risk factors could be exposure to biomass fuel (in females), air pollution, occupational factors, etc. There are few studies that really characterise smoker & non-smoker COPD phenotype so that treatment can be individualised. Aim-The study was designed to assess phenotypic differences between smoker & non-smoker COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated that COPD patients who were smokers had more symptoms of chronic cough and sputum than non-smokers. [38][39][40] This also highlights the importance of quitting smoking. Smoking cessation not only prevents COPD development but also slows COPD progression, regardless of severity.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have indicated that COPD patients who were smokers had more symptoms of chronic cough and sputum than non-smokers. [38][39][40] This also highlights the importance of quitting smoking. Smoking cessation not only prevents COPD development but also slows COPD progression, regardless of severity.…”
Section: Discussionmentioning
confidence: 92%